Effect of mercury on selenium binding to rat lens proteins in vitro - Ostádalová, I; Babický, A; Kopoldová, J; Zímová, M (Physiologia Bohemoslovaca, 1989)
The effect of mercury in the incubation medium on selenium influx, efflux and distribution was studied in eye lenses of 14-day-old rats. The presence of mercury did not affect the uptake of selenium into a water-soluble protein fraction but increased considerably its content in water-insoluble proteins and thus also the selenium influx into experimental lenses. The efflux from experimental lenses yielded significantly lower amounts of released selenium, most of the selenium being bound to proteins. In contrast, efflux experiments with control lenses showed most of the selenium to be in the medium in the form of free anions. The selenium content in experimental lenses decreased after the efflux only in the fraction of water-soluble proteins, while the decrease in control lenses was found in both fractions and was relatively higher in water-insoluble proteins. During both influx and efflux experiments the lenses of both groups released a small of proteins, but no difference found between the two groups.
Keywords: Lens, Crystalline; rtuť; velikost orgánu; krysa rodu Rattus; techniky in vitro; krystaliny; Selenium; oční čočka; Animals; selen; Mercury; Crystallins; inbrední kmeny potkanů; Rats, Inbred Strains; Organ Size; zvířata; In Vitro Techniques; Rats